The Deterrent Effect of Antitrust Enforcement - Block, Michael Kent; Nold, Frederick Carl; Sidak, Joseph Gregory (Journal of Political Economy, 1981)
In this paper we formulate and test a model of collusive pricing in the presence of antitrust enforcement. We show that a cartel's optimal price is likely to be neither the competitive price nor the price that the cartel would set in the absence of antitrust enforcement but rather an intermediate price that depends on the levels of antitrust enforcement efforts and penalties. Our empirical results reveal that increasing antitrust enforcement in the presence of a credible threat of large damage awards has the deterrent effect of reducing mark-ups in the bread industry.